HATE SPEECH FOR THE PURPOSE OF CREATING HOSTILITY IN INDONESIAN COMMUNITIES (Study of Criminalization and Legal Reality According to Criminal Law Experts) - Maradingin Maradingin; Pagar Pagar; Jamil Jami (State Islamic University of North Sumatra Indonesia, 2019)
Especially printed media sheets and electronic media monitors, as well as direct educational exposure, always fulfills important information presentations that are sometimes mixed with Hate speech in the digital age, and democratization is growing very rapidly lately. In addition to its many benefits, it will also be able to threaten the integrity of the nation. Hate speech (hate speech) can trigger the occurrence; riots, hostilities, fights, even wars. This research has some influence, because the previous article